Exploring young children's performance on and acceptance of an educational scenario-based digital game for teaching route-planning strategies: a case study. Issue 8 (16th November 2016) - Lin, Yi-Hui; Hou, Huei-Tse
Abstract : Researchers suggest that game-based learning (GBL) can be used to facilitate mathematics learning. However, empirical GBL research that targets young children is still limited. The purposes of the study is to develop a scenario-based digital game to promote children's route-planning ability, to empirically explore children's learning performance in route planning through the game, and to probe children's technology acceptance of the game. A total of 71 children participated in the study, and both qualitative and quantitative approaches were used, including an interview analysis as well as performance and content analyses of learners' route-planning tasks. The findings showed that the game had a positive effect on children's learning of route-planning strategies, that children's route-planning strategies were improved with the support of the game, and that children demonstrated high technology acceptance toward the game. This study may be of importance in offering insight into children's GBL.